ASSOCIATION BETWEEN HEART RATE VARIABILITY AND COMPONENTS OF THE METABOLIC SYNDROME IN WOMEN WITH RHEUMATOID ARTHRITIS - D. S. Novikova; T. V. Popkova; A. N. Gerasimov; A. V. Volkov; E. L. Nasonov (Столичная издательская компания, 2015)
Aim. To study the relationship between heart rate variability (HRV) and components of the metabolic syndrome (MS) in women with rheumatoid arthritis (RA). Material and methods. Female patients (n=291) with a firm RA diagnosis under 60 years of age were examined. Evaluation of traditional cardiovascular risk factors, MS components (International Diabetes Federation criteria), 24-hour ECG monitoring were performed along with the assessment of clinical symptoms, the degree of activity and severity of RA. Results. Weak associations of HRV with waist circumference, blood pressure level, hypertriglyceridemia, hypoalphalipoproteinemia and smoking were found in the correlation analysis. Patients with RA were divided into three groups depending on the number of existing MS components. Group 1 (0-1 component) included 113 women (39%), group 2 (2-3 components) - 109 women (37%) and group 3 (4-5 components) - included 69 women with RA (24%). Progressive decrease in the absolute values and the increase in the percentage of the low values of all the studied time and frequency HRV indices, adjusted by age and heart rate, from the 1st to the 3rd group of women with RA were determined. Significant increase in sympathovagal index from the 1st to the 3rd group was also shown. Conclusion. A combination of several components of the MS in RA plays a greater role in the development of disorders of neurovegetative autonomic control of heart activity (increased influence of the sympathetic and/or reduced influence of the parasympathetic nervous system on cardiac function) than each traditional cardiovascular risk factor taken separately. Abnormality in autonomic regulation of cardiac activity may be an important link in the pathogenesis of cardiac arrhythmias, sudden cardiac death and overall cardiovascular mortality in women with RA.